Factors Influencing the Job Satisfaction of Health System Employees in Tabriz, Iran - Shokoufe Bagheri; Ahmad Kousha; Ali Janati; Mohammad Asghari-Jafarabadi (Tabriz University of Medical Sciences, 2012)
Background: Employees can be counseled on how they feel about their job. If any particular dimension of their job is causing them dissatisfaction, they can be assisted to appropriately change it. In this study, we investigated the factors affecting job satisfaction from the perspective of employees working in the health system and thereby a quantitative measure of job satisfaction.Methods: Using eight focus group discussions (n=70), factors affecting job satisfaction of the employees were discussed. The factors identified from literature review were categorized in four groups: structural and managerial, social, work in it-self, environmental and welfare factors.Results: The findings confirmed the significance of structural and managerial, social, work in it-self, environmental and welfare factors in the level of job satisfaction. In addition, a new factor related to individual characteristics such as employee personal characteristics and development was identified.Conclusion: In order to improve the quality and productivity of work, besides, structural and managerial, social, work in it-self, environmental and welfare factors, policy makers should be taken into account individual characteristics of the employee as a factor affecting job satisfaction.